Finding a job - Ferguson Publishing (New York : Ferguson, 2010)
'Locating a job takes time, planning, careful research, and dedication. Finding a Job gives readers the tools, resources, and information they need to land their dream job. Readers will learn how to research career options, match their personality with careers, network, write cover letters and rum, perform well on interviews, and much more.'--Publisher's web site.
Who am I? : matching your personality, interests, and skills with a career -- Obtaining experience before you enter the workplace -- Researching career options -- Networking and tapping the hidden job market -- Writing effective cover letters, resumes, and career portfolios -- What to do before, during, and after the job interview -- Assessing a job offer -- You're hired! Now what?
Includes bibliographical references (p. 197-206) and index
Keywords: Job hunting -- Juvenile literature; Occupations -- Juvenile literature; Vocational guidance -- Juvenile literature; Job hunting; Occupations; Vocational guidance